B-CAk In Speeding Up Business Rate In The Beginning Of Small Beginners In The Era: B-CAk In Speeding Up Business Rate In The Beginning Of Small Beginners In The Era - Nurul Lathifah (Jurnal Mantik, 2020)
The large potential of SMEs needs to be made effective as the driving force of the national economy. However, efforts to develop SMEs still encounter various obstacles. Accounting is an important factor in developing SMEs has not been done much. The use of accounting information in decision making will affect company performance. The object of this research is the internal business environment, strategic planning, especially in the financial sector, as well as the development of the newly established Small and Medium Enterprises (SMEs). The founders of SMB beginners are generally new people in the business. Therefore, there are many problems faced in starting and building their business, especially in terms of managing finances. This research specifically identifies the problems faced by the founding SME founders. The research method used in this research is the case study method. Data collection techniques used were field research consisting of observations and interviews. To overcome this problem, the Accounting Record Book (B-CAk) can be an easy solution. B-CAk is a tool that helps financial records for novice entrepreneurs. This book is designed for beginner entrepreneurs who are just starting a business so that they are still unfamiliar with recording and accounting activities. This book is useful for providing the information needed by business owners in conducting their business activities so that it helps the decision-making process. B-CAk contains 6 records that are important in decision making, namely cash flow records, income statements, and balance sheets (includes a list of assets, debts, receivables, and capital). Financial reporting is absolutely necessary if a business wants to develop. SMEs who develop their businesses are required to make financial reports. B-CAk is one alternative. B-CAk was created with the aim that SMEs can easily make financial reports.